5x-6y=0

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 5x from both sides of the equation.

-6y=-5x

Divide each term by -6 and simplify.

Divide each term in -6y=-5x by -6.

-6y-6=-5x-6

Cancel the common factor of -6.

Cancel the common factor.

-6y-6=-5x-6

Divide y by 1.

y=-5x-6

y=-5x-6

Dividing two negative values results in a positive value.

y=5×6

y=5×6

Rewrite in slope-intercept form.

y=56x

y=56x

Using the slope-intercept form, the y-intercept is 0.

b=0

Find the Y-Intercept 5x-6y=0